Shape of transition layers in a differential--delay equation - Wattis, Jonathan A.D. (Oxford University Press, 2017)
We use asymptotic techniques to describe the bifurcation from steady-state to a periodic solution in the singularly perturbed delayed logistic equation εx˙(t) = −x(t)+ λ f(x(t − 1)) with ε ≪ 1. The solution has the form of plateaus of approximately unit width separated by narrow transition layers. The calculation of the period two solution is complicated by the presence of delay terms in the equation for the transition layers, which induces a phase shift that has to be calculated as part of the solution. High order asymptotic calculations enable both the shift and the shape of the layers to be determined analytically, and hence the period of the solution. We show numerically that the form of transition layers in the four-cycles is similar to that of the two-cycle, but that a three-cycle exhibits different behaviour.